Hubungan Faktor Sosiodemografi dengan Pengetahuan dan Sikap terhadap Deteksi Dini Kanker Serviks pada Perempuan di Wilayah Pasca Bencana: Implikasi bagi Pemulihan Layanan Kesehatan Preventif - Sintikhewati Yenly Sucipto; Novita Wulandari (STIKES Ngesti Waluyo, 2026)
Cervical cancer is a preventable disease; however, its incidence and mortality remain high worldwide. Limited access to healthcare services and the shift in healthcare priorities following disasters may reduce the utilization of cervical cancer screening. This cross-sectional analytical study was conducted among 76 women aged 15–49 years living in a post-disaster area. Data were collected using a structured questionnaire and analyzed using the Chi-square test and multivariable logistic regression to identify factors independently associated with knowledge and attitudes toward cervical cancer screening. Overall, 50.0% of participants had good knowledge, and 64.5% demonstrated a positive attitude toward cervical cancer screening. Age and educational level were significantly associated with knowledge (p<0.05), whereas only age was significantly associated with attitudes toward cervical cancer screening (p=0.017). Multivariable analysis showed that women aged 15–24 years were less likely to have good knowledge (AOR=0.031; 95% CI: 0.004–0.243; p=0.001) and a positive attitude toward cervical cancer screening (AOR=0.148; 95% CI: 0.036–0.615; p=0.009). Strengthening continuous and targeted health education for younger women and those with lower educational attainment should be integrated into post-disaster health service recovery to improve the uptake of cervical cancer screening.